A microstructural investigation into the accelerated corrosion of P91 steel during biomass co-firing. (August 2016) - O'Hagan, Conor P.; O'Brien, Barry J.; Leen, Sean B.; Monaghan, Rory F.D.
Highlights: Chemical and microstructural investigation into accelerated corrosion of P91 during biomass co-firing. Chlorine and potassium contents of ash shown to have significant detrimental impacts on corrosion mechanisms and damage. SEM investigation of corrosion-induced cracking in oxide scales. Demonstration of interaction of inclusions and chlorine-containing ash in pitting corrosion. Finite-element prediction of plasticity due to inclusion-matrix thermal mismatch. Abstract: This work presents results of an in-depth experimental microstructural characterisation of P91 steel, following exposure to salts representative of ash produced during biomass co-firing. The ash produced during co-firing contains high levels of harmful elements such as potassium, sodium and chlorine, which result in the accelerated corrosion of heat exchanger tubes in fluidized bed power plants. Synthetic salts representative of 70:30 peat-biomass and 40:60 peat-willow mixtures have been produced and applied to samples at 600 °C in air for up to 28 days. Samples have been etched to reveal the steel microstructure, allowing for a comprehensive evaluation of microstructural degradation of the samples. Cracks associated with the delamination of scales have been identified at the oxide-metal interface, with multiple layers of oxides forming as a result. A number of pits have been identified in the samples, which are associated with inclusions located close to the sample surface. Finite element analysis of the effect of differential thermal expansion coefficients between the inclusions and base metal shows the detrimental effect of such inclusions, leading to stress concentrations at the inclusion-metal interface.